TPocket Parks for Enhancing Residents’ Social Interaction in the City of Baghdad, Iraq - Abdulkareem Salih, Sarah; Ismail, Sumarni; Atiah Ismail, Nor (International Journal of Engineering and Technology, 2026)
This paper addresses the issue of lack of public open spaces, which led to decrease social interaction among residents in the city of Baghdad nowadays. The objective of this paper is to determine the criteria and benefits of the nearby public green open spaces (pocket parks) to enhance social interaction of users in the city of Baghdad. This study employed text content analysis method of (Mayring, 2014). The required data collected from text documentation including articles, papers and research study regarding the importance of public nearby open spaces for the community interactions. The content analysis is also used to analyze the information gathered. The findings confirm providing an efficient numbers of pocket parks with proper criteria can contribute in increasing residents’ social interaction in the neighborhoods of Baghdad city. These spaces can contribute in the social, health, environmental, recreational and relaxation or mental benefits for the residents of Baghdad.